Internal Factors Affecting Entrepreneurial Interest of IBM-RC Students Universitas Ciputra Surabaya - Abdi, Anastasia Natali (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The number of people who do not have jobs is a in Indonesia, with the continued increase in the number of unemployed, it will weaken the country’s economy because more and more people are without work and are unable to meet their daily needs therefore entrepreneurs are needed to create jobs to reduce unemployment. To become an entrepreneur, several factors are needed to foster interest in entrepreneurship, both internal and external factors. The purpose of this study was to determine and analyze the internal factors that influence the entrepreneurial intention of International Business Management-Regular Class students at Ciputra University Surabaya. The method used in this study is a quantitative method by distributing online questionnaires. The sample in this study were 97 IBM-RC students Ciputra University Surabaya. The results of this study indicate that personality, self-efficacy, entrepreneurial motivation and entrepreneurship attitude are internal factors that influence the entrepreneurial intention of IBM-RC students Ciputra University Surabaya, while risk taking is not a factor that affects the entrepreneurial intention of IBM-RC students Ciputra University Surabaya.